Serguey Zhadan’s Melancholic Nomadism and National Imagination in Ukraine - Korchagin, Kirill (Przegląd Wschodnioeuropejski, 2018)
A recent state crisis in Ukraine launched the process of the re-treatment of national and state borders not only in public politics and media, but also in culture and literature. According to Deleuze and Guattari, contemporary humans live in the epoch when nomadic subjectivity comes on the scene in order to change the regime of national spatial imagination. Nomadic existence regarding individuals as always “on the road” seems to be a tool for the de- and re-territorialization that shapes new cultural and state borders. This paper regards Serhiy Zhadan, one of the most prominent contemporary Ukrainian poets, and his treatment of the Ukrainian nation and its borders. For Zhadan, the need for poetry practice has to participate in the nation-building process intensified after Maidan. The key concept for this process’s comprehension is melancholia, which could help to draw an image of contemporary Ukranian subjectivity.